Mining task analysis: Mechanical and metabolic considerations in a deep Canadian mechanized mine - Mate, Joseph E (University of Ottawa (Canada), 2007)
Purpose. The objective of this thesis was to examine work in mines. Specifically, part #1 performed in-situ time/motion analyses of common mining jobs and part #2 analyzed in-situ energy expenditures while working in a mine. Methodology. Part #1- task and sub-task duration and subjective work intensity were investigated for thirty eight subjects from six different mining jobs. These jobs were then organized into 4 groups for statistical analysis based on precedence: Group 1 (Bolting & Screening (attaching steel mesh to walls and ceiling), Group 2 (Conventional Mining (using a hand-held drilling carriage to drills holes in rock walls and ceiling)), Group 3 (Support Services (mechanic, welder, pipe layer)), Group 4 (Production Drill (using a machine mounted drilling unit), Scooptram(TM) (ore transport with no air conditioner), Shotcrete (concrete applied by spraying)). Part #2- In-situ metabolic energy expenditures were estimated through indirect open circuit calorimetry and deep tissue and skin temperatures were measured for those same groups. Results. Part #1- twenty three common mining tasks were identified with differences identified between various group for time and intensity. Part #2- metabolic requirements between groups were similar with one difference identified between groups 3 and 4 (P < 0.05). Deep tissue and skin temperatures did not change significantly through the course of a work day. Conclusion. Part #1- a variety of tasks is performed by each group and there is no uniform work protocol. Part #2- each mining group's metabolic energy expenditure requirements to perform various mining tasks are similar.
Keywords: Health Sciences, Occupational Health and Safety.; Engineering, Mining.